(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The development of the article aims to advance a socio-legal analysis of how informality in the workplace has a major impact on the non-fulfilment of the right to housing in decent and adequate conditions for the population of the Municipality of Ibagué - Colombia. Informal work, as is well known, is an important factor in the economy and in the development of Ibagué society, especially in a city like Ibagué, which has high rates of unemployment in Colombia as well as a high number of people working in the informal sector. The main conclusions are the need to strengthen the legal system in order to satisfy the right to housing as established in the Constitution and those parameters and guidelines suggested by international organisations that should be taken into account in the design of public policy, as well as the need to avoid discrimination and promote equality in order to facilitate access to decent housing.